Distinction : a social critique of the judgement of taste - Bourdieu, Pierre, 1930-2002. (London : Routledge, 2010)
In 'Distinction', Pierre Bourdieu brilliantly illuminates the social pretentions of the middle classes in the modern world. Focusing on the French bourgeoisie - its tastes and preferences - 'Distinction' is at once a vast ethnography of contemporary France and a dissection of the bourgeois mind.
Originally published: Routledge Kegan & Paul, 1984.
Includes bibliographical references and index.
Translated from the French.
Keywords: Middle class -- France; Aesthetics, French; Judgment (Aesthetics); France -- Civilization -- 1945-